1981
DOI: 10.1007/bf00127203
|View full text |Cite
|
Sign up to set email alerts
|

Methylene-blue/Coriphosphine-O/Acridine-Orange, chromosomal DNA and visible light: Interaction and cytological effect in Drosophila melanogaster

Abstract: Metaphase preparations of Drosophila melanogaster were irradiated with visible light in the presence of either Methylene-blue, Coriphosphine-0 or Acridine-Orange. After treatment with any of these three compounds, Coriphosphine-0 staining shows an identical green/ orange-red/ brown-red chromosome pattern. These findings are discussed in the light of previous reports and guanine destruction is hypothesized as representing the most plausible mechanism for explaining the cytological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This corresponds well with the high amount of pectin (mainly rhamnogalaturonans) present in soybeans (Huisman et al, 1998(Huisman et al, , 2003. Besides being used as a stain for detection of pectin in plant sources (Mosele et al, 2011), coriphosphine O is known to stain other cell components such as DNA and RNA (Mezzanotte et al, 1981) which can also be seen as labelling of nuclei in Figure 2B. Alcian blue is a dye with high affinity for pectic substances (Gunawardena et al, 2007;Arend et al, 2008) and was used to support the results found with coriphosphine O staining showing pectin solubilisation.…”
Section: Discussionmentioning
confidence: 54%
“…This corresponds well with the high amount of pectin (mainly rhamnogalaturonans) present in soybeans (Huisman et al, 1998(Huisman et al, , 2003. Besides being used as a stain for detection of pectin in plant sources (Mosele et al, 2011), coriphosphine O is known to stain other cell components such as DNA and RNA (Mezzanotte et al, 1981) which can also be seen as labelling of nuclei in Figure 2B. Alcian blue is a dye with high affinity for pectic substances (Gunawardena et al, 2007;Arend et al, 2008) and was used to support the results found with coriphosphine O staining showing pectin solubilisation.…”
Section: Discussionmentioning
confidence: 54%
“…Acridine orange (Cambier, Wheeless & Patten, 1977; Fukuda et al. , 1979, 1986; Mezzanotte, Ferrucci & Marchi, 1981; Miyoshi & Fukuda, 1986), aminoacridines (Blake & Peacocke, 1968), acriflavine (Roth, 1976) or proflavine (Sagawa & Tatsumi, 1997) can be used to detect DNA by fluorescence. Acridine orange, acridine yellow or choriphosphine O are also used to detect RNA by metachromatic fluorescence (Bradley & Wolf, 1959).…”
Section: Discussionmentioning
confidence: 99%